The Influence of Learning Facilities and Learning Environment on the Learning Motivation of Class VIII Students at SMP Negeri 7 Pematang Siantar - Siska Veronika; Anton Luvi Siahaan; Tumpal Manahara Siahaan (MultiTech Publisher, 2023)
This research aims to determine the influence of learning facilities and learning environment on the learning motivation of class VIII students at SMP Negeri 7 Pematang Siantar. The variables in this research are learning facilities and learning environment as independent variables and learning motivation income as the dependent variable. Meanwhile, the type of research used by researchers is correlational, with the research population being all class VIII students at SMP Negeri 7 Pematang Siantar consisting of 223 students. From the population, the sample for this research was random sampling (random sample) using the Slovin formula, namely 146 students. Data collection techniques use instruments: (1) learning facilities questionnaire, (2) learning environment questionnaire, and (3) learning motivation questionnaire. The results of this research show that: (1) there is a positive and significant influence of learning facilities on learning motivation, this result can be seen in the t test where the t value is > t table ( 3.388 >1.976 ) and the value is significant (0.0 01<0.05) . (2) there is a positive and significant influence of the learning environment on learning motivation, this result can be seen in partial calculations (t test) on the learning environment (X 2 ) showing the calculated t value <t table( -2,240 <1, 976 ) and significant value (0, 027 > 0.05) . (3) Learning Facilities and Learning Environment on the Learning Motivation of Class VIII Students of SMP Negeri 7 Pematang Siantar. This can be seen from the results of simultaneous calculations(F test) on Learning Facilities (X 1 ) and learning environment (X 2 ) was carried out using SPSS 21.0, namely showing the calculated f value > f table ( 5.776 >1.655 ) and significant value (0.004 <0.05 .